(Table T1) Carbonate and opal composition of ODP Hole 198-1208A sediments, Shatsky Rise - Stuart A Robinson; Hugh C Jenkyns (PANGAEA, 2005)
Weight percent opal and carbonate data are presented for the Miocene-Lower Pliocene interval at Site 1208 on Shatsky Rise. These data compare favorably with shipboard estimates and measurements. The opal and carbonate data confirm that the color cycles recognized in shipboard data are the result of fluctuations in carbonate content and are not related to opal productivity.
Supplement to: Robinson, SA; Jenkyns, HC (2005): Data report: Opal and carbonate data from the Miocene to Lower Pliocene, Site 1208 (Central High, Shatsky Rise). In: Bralower, TJ; Premoli Silva, I; Malone, MJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 198, 1-7, https://doi.org/10.2973/odp.proc.sr.198.120.2005